Concurrent claims under Brussels Ibis Regulation - Kravcenko, Aleksandrs Arsenijs (Riga Graduate School of Law, 2021)
This paper is aimed at researching issues associated with how the Regulation (EU) No 1215/2012 of the European Parliament and of the Council of 12 December 2012 on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters deals with concurrent claims, more specifically, the abuse of law under the aforementioned regulation, intricacies which are connected to parallel judicial proceedings and what possible solutions there might be. In this paper, the author looks into the relevant provisions of the Regulation, judgments of the Court of Justice and opinions of scholars on the issue in order to find out how the current regulatory regime is functioning, what drawbacks it exhibits and understand whether there still is room for improvement.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law